HIV detection by an emergency department HIV screening program during a regional outbreak among people who inject drugs. - Kiran A Faryar (Public Library of Science (PLoS), 2021)
Objective Multiple HIV outbreaks among persons who inject drugs (PWID) have occurred in the US since 2015. Emergency departments (EDs), recognized as essential venues for HIV screening, may play a unique role in identifying undiagnosed HIV among PWID, who frequently present for complications of injection drug use (IDU). Our objective was to describe changes in HIV diagnoses among PWID detected by an ED HIV screening program and estimate the program's contribution to HIV diagnoses among PWID county-wide during the emergence of a regional HIV outbreak. Methods This was a retrospective study of electronically queried clinical records from an urban, safety-net ED's HIV screening program and publicly available HIV surveillance data for its surrounding county, Hamilton County, Ohio. Outcomes included the change in number of HIV diagnoses and the ED's contribution to case identification county-wide, overall and for PWID during 2014-2018. Results During 2014-2018, the annual number of HIV diagnoses made by the ED program increased from 20 to 42 overall, and from 1 to 18 for PWID. We estimated that the ED contributed 18% of HIV diagnoses in the county and 22% of diagnoses among PWID. Conclusions The ED program contributed 1 in 5 new HIV diagnoses among PWID county-wide, further illustrating the importance of ED HIV screening programs in identifying undiagnosed HIV infections. In areas experiencing increasing IDU, HIV screening in EDs can provide an early indication of increasing HIV diagnoses among PWID and can substantially contribute to case-finding during an HIV outbreak.